Moral realism, quasi‐realism and moral steadfastness. (Ratio, 2022)
Some moral propositions are so obviously true that we refuse to doubt them, even where we believe that many people disagree. Following Fritz and McPherson, I call our behaviour in such cases 'moral steadfastness'. In this paper, I argue for two metaethical implications of moral steadfastness. I first argue that morally steadfast behaviour is sufficiently prevalent to present an important challenge for some prominent analogies between moral epistemology and non‐moral forms of epistemology. These analogies are often pressed by moral realists. I then argue that moral quasi‐realism, unlike realism, can explain and vindicate our presumption that moral steadfastness is frequently rational. On the assumption that we frequently act as it is rational to act, quasi‐realism is therefore well placed to explain why we are so frequently morally steadfast. I conclude that this is an important respect in which quasi‐realism is explanatorily preferable to realism.